An Analysis of the Garment sector of Pakistan within a Global Value Chain Framework - Malik, Kashif; Turab Hussain, Syed; Faheem, Adeel; Khan, Usman (ExcelingTech, 2019)
The textile industry is Pakistans largest and one of the oldest manufacturing industries. Widely available local cotton and continuous public support have been important factors in the growth of the textile industry. However, the garment sector in Pakistan is trapped at a low-equilibrium in a high value-added categoryproducing low-price items for mass retailers. The objective of this paper is to identify the main reasons for the relative stagnation and lack of competitiveness of Pakistans garments sector in light of survey data collected form 234 garments manufacturers. We use Global Value Chain (GVC) framework to analyze Pakistans garment industry. To come out of low-equilibrium and move up the garments value chain, the sector requires continual investment in state of the art technology, a trained workforce, and agglomeration economies or intra-cluster spill-overs.